Implementasi Metode Forward Chaining Untuk Mendiagnosa Penyakit Tumor Otak - Isarianto; Melinda Indriani (Prosiding Sains dan Teknologi, 2025)
Expert systems can assist people in conducting early disease diagnosis by simulating expert knowledge in answering questions and providing solutions. This web-based application enables users to obtain analysis results regarding appropriate treatment and necessary medical actions based on their symptoms. At Central Medika Hospital, consultations are limited to specific doctor practice hours and involve relatively high fees. As a result, patients experiencing symptoms such as severe headaches resembling brain tumor indications outside practice hours must wait for examination, potentially delaying treatment. To address this issue, a brain tumor diagnostic expert system was developed using a rule-based approach with the Forward Chaining algorithm. The system was built using the Waterfall development method, with MySQL as the database and PHP and HTML as the programming languages. The research involved two types of testing: functional testing using Black-box testing and accuracy testing of the Forward Chaining calculations. The results showed that the system functioned very well, and the accuracy test achieved a result of 100%, indicating that the system’s diagnostic conclusions were fully consistent with the predefined rules.